MANFAAT KAJIAN GERABAH MASA LALU BAGI PENGEMBANGAN KERAJINAN TEMBIKAR SEBAGAI PENUNJANG INDUSTRI PARIWISATA - Sumijati Atmosudiro (Berkala Arkeologi, 1998)
In line with the development of Indonesian archaeology, the interest in archaeological research is not only focused on monumental, but also on non-monumental remains such as the pottery. This is evidenced by the many studies on pottery in the form of articles, theses and dissertations. As a result of the many researches on pottery, there are problems that need to be solved, especially the problem of the benefits of the study of past pottery in relation to the development of today's pottery handicrafts. In turn, the results of this development can be used as an asset that supports the tourism industry. In order to solve this problem, it is necessary to outline the results of the study of past pottery and traditional pottery.